The private accuser and the principle of equality of arms: a critique of Colombia’s legal system - Diez Rugeles , Miguel; Vivares Porras , Luis Felipe (Revista de la Facultad de Derecho y Ciencias Políticas, 2020)
The Ley 1826 de 2017 (Law 1826 of 2017) introduces two novel institutions to our legal system: the abbreviated procedure and the private accuser. This last institution allows the victim’s representative to shift from intervening party to procedural part, this supposes changes on the initial legal conditions that necessarily impact his counterpart: the accused. This impact is predominantly noticeable when regarding the principle of equality of arms. Questions regarding the equality of conditions between the parties to a criminal trial arise before institutions such as the principle of objectivity in the investigation, the discovery of evidence, the burden of proof, the acts of investigation, and the controls of the latter. This paper intends to answer if within the framework of the abbreviated criminal procedure with the presence of a private accuser, the defense can request, exactly as the counterpart is allowed, the execution of complex investigation acts, in accordance to the structure of the Colombian criminal process and the principles that guide it. Thus, a contribution regarding the investigative powers of the parties in the Colombian criminal process that interest academics would be made; but also, to the operators of the penal system.